2016
DOI: 10.12740/app/66519
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of eating disorders with the use of classification trees (decision algorithm)

Abstract: SummaryBackground: The aim of the study was to establish whether it is possible to make a correct diagnosis of various types of eating disorders on the basis of several variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A search of electronic materials, including journal articles, dissertations, and other available electronic and print sources, yielded candidate articles that were ultimately included in this synthesis if they (a) administered the third edition of the EDI (EDI‐3, Garner, 2004), (b) used the English version of the EDI‐3, and (c) provided some form of score reliability or validity data on the sample under study. In the review of the existing literature, translated versions of the EDI‐3 were found in Danish (Clausen et al., 2011; Staal et al., 2018), Finnish/Swedish (Ålgars et al., 2015; Lindberg et al., 2018), French (Ostiguy et al., 2017; Prost‐Lehmann et al., 2018; Turgeon et al., 2015), German (Waldorf et al., 2014), Italian (Ambrosecchia et al., 2017; Buzzichelli et al., 2018; Cesare et al., 2016; Dakanalis et al., 2015; Fortunato et al., 2017; Novara et al., 2017; Zanna et al., 2017), Japanese (Ito et al., 2016), Mandarin Chinese (Meng et al., 2020; Wang et al., 2015), Polish (Izydorczyk, 2011), Portuguese (Torres et al., 2017), and Spanish (Cuesta‐Zamora et al., 2018; Elosua et al., 2012). Because it was unclear if these other‐language versions conformed to best practice translations procedures (American Educational Research American et al., 2014), only those studies using the English version of the EDI‐3 were included in this synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…A search of electronic materials, including journal articles, dissertations, and other available electronic and print sources, yielded candidate articles that were ultimately included in this synthesis if they (a) administered the third edition of the EDI (EDI‐3, Garner, 2004), (b) used the English version of the EDI‐3, and (c) provided some form of score reliability or validity data on the sample under study. In the review of the existing literature, translated versions of the EDI‐3 were found in Danish (Clausen et al., 2011; Staal et al., 2018), Finnish/Swedish (Ålgars et al., 2015; Lindberg et al., 2018), French (Ostiguy et al., 2017; Prost‐Lehmann et al., 2018; Turgeon et al., 2015), German (Waldorf et al., 2014), Italian (Ambrosecchia et al., 2017; Buzzichelli et al., 2018; Cesare et al., 2016; Dakanalis et al., 2015; Fortunato et al., 2017; Novara et al., 2017; Zanna et al., 2017), Japanese (Ito et al., 2016), Mandarin Chinese (Meng et al., 2020; Wang et al., 2015), Polish (Izydorczyk, 2011), Portuguese (Torres et al., 2017), and Spanish (Cuesta‐Zamora et al., 2018; Elosua et al., 2012). Because it was unclear if these other‐language versions conformed to best practice translations procedures (American Educational Research American et al., 2014), only those studies using the English version of the EDI‐3 were included in this synthesis.…”
Section: Methodsmentioning
confidence: 99%